Pembelajaran Karawitan Pada Kelas Reguler C di Sanggar Karawitan Cakra Aji Kabupaten Tulungagung - ega; Bambang Sugito (Jurnal Pendidikan Sendratasik, 2025)
Cakra Aji Karawitan Studio is an institution established to provide a platform for the younger generation of Tulungagung to develop their traditional Javanese karawitan skills through a structured and progressive learning process. By implementing culture-based learning, the studio also offers opportunities for artistic expression, particularly in Regular Class C, an advanced-level class focusing on the study of gendhing ladrang. This study aims to describe comprehensively the implementation of learning in Regular Class C in studying gendhing ladrang, including the instructional methods employed. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation of the learning activities in Regular Class C. The validity of the data was ensured through source, technique, and time triangulation. The data sources consisted of both primary and secondary data. The collected data were analyzed using three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the learning process in Regular Class C at Cakra Aji Karawitan Studio applies a formal instructional system supported by three learning stages: preliminary activities, core activities, and closing activities. Throughout the learning process, the instructor implements lecture, demonstration, and drill methods to facilitate students' mastery of gendhing ladrang.